Noninvasive biomarkers in NAFLD and NASH — current progress and future promise - Wong, Vincent Wai-Sun (2018)
Nonalcoholic fatty liver disease (NAFLD) affects 25% of the global adult population and is the most common chronic liver disease worldwide. Nonalcoholic steatohepatitis (NASH) is the active form of NAFLD, with hepatic necroinflammation and faster fibrosis progression. With an increasing number of patients developing NASH-related end-stage liver disease and pharmacological treatments on the horizon, there is a pressing need to develop NAFLD and NASH biomarkers for prognostication, selection of patients for treatment and monitoring. This requirement is particularly true as liver biopsy utility is limited by its invasive nature, poor patient acceptability and sampling variability. This article reviews current and potential biomarkers for different features of NAFLD, namely, steatosis, necroinflammation and fibrosis. For each biomarker, we evaluate its accuracy, reproducibility, responsiveness, feasibility and limitations. We cover biochemical, imaging and genetic biomarkers and discuss biomarker discovery in the omics era.